Aquatic insect β-diversity among small mountain headwater streams and the role of multiple mechanisms maintaining community structure - Harrington, Rachel Anne, author; Poff, N. LeRoy, advisor; Kondratieff, Boris, committee member; Ghalambor, Cameron, committee member (Colorado State University. Libraries, 2014)
Despite lower local richness (α-diversity), individual headwater tributaries often retain highly distinct aquatic insect communities (β-diversity) within the overall river network. This trend is presumed especially true among high-elevation streams; where high β-diversity is driven by the effects of steep topography and harsh climatic conditions limiting dispersal between isolated mountaintop "islands." However, inference has been predominantly drawn from observed trends along single-thread channels (higher-elevation headwaters through lower-elevation mainstems); and the increased size and hydrologic connectivity accompanying lower-elevation mainstems provide potential alternative explanations for this pattern. Controlling for habitat size, I sampled aquatic insect communities in 24 headwater streams from three adjacent river drainages spanning 2000-3500 m in elevation. I measured β-diversity among streams within each drainage (community turnover- β across elevation) and β-diversity across drainages (community dissimilarity- β within elevation "zones"). Turnover- β across elevation was consistently high and displayed no trend. Additionally, dissimilarity-β across drainages was not significantly different between high-elevation and low-elevation zones. These results provide the first evidence that β-diversity among low-elevation headwater communities is equivalent to communities at high-elevations. Evidence suggests that high β-diversity among small headwater streams is attributed to low habitat connectivity and/or to high habitat heterogeneity, resulting from their isolated position within the dendritic network and strong responses to the surrounding environment. In order to disentangle the role of multiple mechanisms maintaining β-diversity, I utilized the unique landscape of mountain ranges, exhibiting steep gradients of spatial distance, local environmental conditions, and disturbance regimes. I characterized all 24 sites using explanatory variables categorized into spatial predictors (describing geographic location), environmental predictors (describing local habitat), and flow regime predictors (describing potential disturbances overtime). Using a series of redundancy analyses (RDA) I tested the ability of each categorized predictor group to significantly explain variation in community structure among those sites within a drainage and among those sites within an elevation zone. Further, original communities were partitioned into unique assemblages distinguished by the presence/absence of key ecological traits. Using interpretation of potential underlying mechanistic processes, I tested a priori hypotheses regarding the change in relationship between trait-partitioned assemblages. Results determined that although environmental predictors best explained community turnover-β within drainages, they were unable to explain community dissimilarity-β within any elevation zone, where habitat heterogeneity is presumably lower and inter-site network distance is higher. Additionally, dissimilarity-β among high-elevation communities was only explained by spatial predictors, supporting previous hypotheses that these communities are isolated by distance, while community dissimilarity-β among low-elevation sites was only explained by flow regime predictors. Overall, these findings suggest that despite consistent patterns in β-diversity, the relative role of mechanisms maintaining this diversity is context dependent, presenting important implications regarding the successful conservation of these dynamic systems.
Keywords: beta-diversity; benthic macroinvertebrates; disturbance; elevation; stream ecology; dispersal